2022
DOI: 10.1111/hsc.14108
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Reablement or restorative homecare interventions  and outcome effects: A systematic review of randomised control trials

Abstract: The effect of Reablement, a multi-faceted intervention is unclear, specifically, which interventions improve outcomes. This Systematic Review evaluates randomised controlled trials (RCTs) describing Reablement investigating the population, interventions, who delivered them, the effect and sustainability of outcomes. Database search from inception to August 2021 included AMED, ASSIA, BNI, CINHALL, EMBASE, HMIC, MEDLINE, PUBMED, PsycINFO, Google Scholar, Web of Science, Clini caltr ials.gov.Two researchers under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A total of 16 systematic reviews (Backhouse et al, 2021 ; Bennett & Hodge, 2021 ; Cochrane et al, 2016 ; Crocker et al, 2021 ; Cunningham et al, 2020 ; Dawson et al, 2020 ; Lucien et al, 2020 ; Malden et al, 2021 ; McGill, Malden, Alex, et al, 2021 ; McGill, Malden, Frost, et al, 2021 ; Montgomery et al, 2008 ; Ogwu et al, 2020 ; Spiers et al, 2019 ; Szczepura et al, 2020 ; Whitehead et al, 2015 ; Young et al, 2017 ) (seven completed and nine ongoing) relevant to research priority topic areas were identified (PROSPERO = 13; Cochrane = 3). Of these, two were reviews of systematic reviews (Cunningham et al, 2020 ; Dawson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 systematic reviews (Backhouse et al, 2021 ; Bennett & Hodge, 2021 ; Cochrane et al, 2016 ; Crocker et al, 2021 ; Cunningham et al, 2020 ; Dawson et al, 2020 ; Lucien et al, 2020 ; Malden et al, 2021 ; McGill, Malden, Alex, et al, 2021 ; McGill, Malden, Frost, et al, 2021 ; Montgomery et al, 2008 ; Ogwu et al, 2020 ; Spiers et al, 2019 ; Szczepura et al, 2020 ; Whitehead et al, 2015 ; Young et al, 2017 ) (seven completed and nine ongoing) relevant to research priority topic areas were identified (PROSPERO = 13; Cochrane = 3). Of these, two were reviews of systematic reviews (Cunningham et al, 2020 ; Dawson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It may also include support to achieve wider goals such as social participation (Jasper et al, 2019 ). Homecare can take the form of long‐term care, or a shorter‐term intervention to facilitate recovery and reablement (Bennett & Hodge, 2021 ; Beresford et al, 2019 ). Although primarily regarded as a social care service, homecare is sometimes coordinated with community health services and can include elements of healthcare (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] There are indications that reablement may be able to reduce the need for ongoing care and permanent admissions. 9,10 Over the last two decades, reablement programs have been studied and implemented partially or fully in 15 countries. 11 In these countries, levels of experience differ, leading to different stages of reablement implementation within each nation.…”
Section: Introductionmentioning
confidence: 99%
“…It is within the context of this global pandemic that students in UK higher education became increasingly isolated in their places of residence, with many unable to work, attend face-to-face university classes or socialise with people outside of their social 'bubble'.Given the reported impact of COVID-19 on student populations in the media, it is not surprising that the topic is starting to be researched (2)(3)(4) . A number of studies (5)(6)(7)(8)(9)(10)(11) examine the correlates of food insecurity among higher education students during COVID-19 lockdown, yet there remains a paucity of research conducted in the UK. This research seeks to fill that gap in the UK literature by investigating those factors associated with food insecurity among a representative sample of UK university students during 2020.…”
mentioning
confidence: 99%
“…Given the reported impact of COVID-19 on student populations in the media, it is not surprising that the topic is starting to be researched (2)(3)(4) . A number of studies (5)(6)(7)(8)(9)(10)(11) examine the correlates of food insecurity among higher education students during COVID-19 lockdown, yet there remains a paucity of research conducted in the UK. This research seeks to fill that gap in the UK literature by investigating those factors associated with food insecurity among a representative sample of UK university students during 2020.…”
mentioning
confidence: 99%